2010
DOI: 10.1007/s00256-009-0873-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided treatments for chronic Achilles tendinopathy: an update and current status

Abstract: Minimally-invasive treatments for chronic Achilles tendinopathy may prevent the need for surgery when conservative methods have failed. Whilst injections have traditionally been used to manage symptoms, recently described therapies may also have disease-modifying potential. Ultrasound provides the ability to guide therapeutic interventions, ensuring that treatment is delivered to the exact site of pathology. Treatments can be broadly categorised according to their intended therapeutic targets, although some ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
0
15
0
3
Order By: Relevance
“…Using ultrasound, a number of interventional procedures can be accurately performed in order to treat Achilles tendinosis. 4,7,34 The ultrasound-guided techniques can be combined and enhanced by physical therapy such as eccentric loading 35,36 (Table 1). Eccentric loading exercises have been shown to be beneficial unless the Achilles tendinosis is of the insertional type.…”
Section: Ultrasound-guided Intervention For the Achilles Tendonmentioning
confidence: 99%
“…Using ultrasound, a number of interventional procedures can be accurately performed in order to treat Achilles tendinosis. 4,7,34 The ultrasound-guided techniques can be combined and enhanced by physical therapy such as eccentric loading 35,36 (Table 1). Eccentric loading exercises have been shown to be beneficial unless the Achilles tendinosis is of the insertional type.…”
Section: Ultrasound-guided Intervention For the Achilles Tendonmentioning
confidence: 99%
“…Retrocalcaneal bursal injection has been used effectively to relieve pain from insertional tendinopathy. 23,24 The technique used for the tendon sheath injection translates to bursal injections as well, and a 25-gauge 1.5-inch needle may be used in most cases. The patient can be placed in either the lateral decubitus with the operator using the medial approach or in the prone position with the feet hanging off the bed; in this position, the operator can use either the medial or lateral approach.…”
Section: Bursal Injectionmentioning
confidence: 99%
“…In the more chronic situation, and especially when there is concurrent tendonosis, a tendon sheath stripping procedure may be performed (also termed tendon brisement and hydrostatic decompression; Figure 2). This is performed with a combination of local anaesthetic and saline, which may include a cortico-steroid [34]. High volume injections of up to 50 ml have been advocated in an attempt to break down adhesions [35].…”
Section: Paratendonitismentioning
confidence: 99%
“…These techniques have been used to treat tendonopathy and neural induced pain syndromes [18,34]. An RCT study of shockwave therapy showed improved outcomes vs eccentric loading physiotherapy for chronic Achilles tendonopathy [65].…”
Section: Other Techniquesmentioning
confidence: 99%